Outcome and Factors Associated with Poor-Grade Subarachnoid Hemorrhage: A Longitudinal Study - Asim Shahzad, Syed Aamir Shah, Rayif Rashid Kanth, Fahmida Arab Mallah, Muzamil, Abdul Razaque Mari (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the factors which determine the outcome of poor-grade subarachnoid hemorrhage. Study design: A longitudinal study Place and Duration: This study was conducted at Pakistan Surgical Center Islamabad Pakistan from April 2020 to April 2021 Methodology: The current study involved 19 patients who had a poor-grade aneurysmal subarachnoid hemorrhage and their different factors were assessed. The inclusion criteria for the study was a diagnosis of poor grade aneurysmal subarachnoid hemorrhage (grade IV or grade V as defined by World Federation of Neurological Surgeons) at the time of admission, confirmation and grading of aneurysmal subarachnoid hemorrhage by CT scans (Fisher grading system), and the aneurysm’s presence has been further confirmed by four-vessel angiography. Results: The incidence of poor-grade patients among all the patients admitted for aneurysmal subarachnoid hemorrhage was 11.89% in our study. We observed that out of 19 patients, 13 had surgeries, and among that, a good outcome was observed in 53.8% of patients. Whereas the 7 patients who were conservatively treated died. Conclusion: If patients with poor-grade aneurysmal subarachnoid hemorrhage are operated (craniotomy with clipping of aneurysm) on within 3 days, they have a 50% chance of giving rise to favorable outcomes.